The vanishing passenger - Warner, Gertrude Chandler, 1890-1979.; Papp, Robert (Morton Grove, Ill. : Albert Whitman, 2006)
When their favorite author fails to arrive as scheduled to speak at the local library, the Alden children investigate how he could board a train and never be seen again.
Keywords: Missing persons -- Fiction; Authors -- Fiction; Brothers and sisters -- Fiction; Orphans -- Fiction; Mystery and detective stories